Benchmarking occupational exoskeletons: An evidence mapping systematic review. (January 2022) - De Bock, Sander; Ghillebert, Jo; Govaerts, Renée; Tassignon, Bruno; Rodriguez-Guerrero, Carlos; Crea, Simona; Veneman, Jan; Geeroms, Joost; Meeusen, Romain; De Pauw, Kevin
Abstract: Objectives: To provide an overview of protocols assessing the effect of occupational exoskeletons on users and to formulate recommendations towards a literature-based assessment framework to benchmark the effect of occupational exoskeletons on the user. Methods: PubMed (MEDLINE), Web of Science database and Scopus were searched (March 2, 2021). Studies were included if they investigated the effect of one or more occupational exoskeletons on the user. Results: In total, 139 eligible studies were identified, encompassing 33, 25 and 18 unique back, shoulder and other exoskeletons, respectively. Device validation was most frequently conducted using controlled tasks while collecting muscle activity and biomechanical data. As the exoskeleton concept matures, tasks became more applied and the experimental design more representative. With that change towards realistic testing environments came a trade-off with experimental control, and user experience data became more valuable. Discussion: This evidence mapping systematic review reveals that the assessment of occupational exoskeletons is a dynamic process, and provides literature-based assessment recommendations. The homogeneity and repeatability of future exoskeleton assessment experiments will increase following these recommendations. The current review recognises the value of variability in evaluation protocols in order to obtain an overall overview of the effect of exoskeletons on the users, but the presented framework strives to facilitate benchmarking the effect of occupational exoskeletons on the users across this variety of assessment protocols. Highlights: This evidence mapping systematic review included 51 validation, 66 evaluation and 22 field assessment papers. Out of the large variation in assessment protocols, an assessment framework was provided. The presented framework facilitates benchmarking the effect of occupational exoskeletons on the users.